Óleo da amêndoa do bacuri microencapsulado por coacervação complexa: desenvolvimento e caracterização - MAYARA PEREIRA VASCONCELOS (2022)
The fruit of the Cerrado and Pantanal bacuri (Attalea phalerata Mart. Ex Spreng) can be a potential vegetable lipid source, since according to the literature the oil of its almonds has 37.9% of medium chain fatty acids, in particular the acid lauric (C12:0). Microencapsulation by complex coacervation has been important to minimize the degradation of bioactive compounds in oils. The aim of the study was to obtain and characterize the oil from bacuri and microencapsulate almonds by complex coacervation. The conservation and quality indexes were determined: saponification, iodine, refraction, acidity and peroxide. The fatty acid profile of bacuri almond oil and microcapsules containing the oil was performed, as well as the development of microcapsules by complex coacervation. The microcapsules were determined according to yield and efficiency, in addition to analyzing the morphology by scanning electron and optical microscopy. The results showed that the best concentration of filling (oil) in relation to the tested polymers (gelatin and gum arabic) was 2.5g for 1.25g of each polymer, in these proportions, yield of microcapsules formed of 70.66 %, oil encapsulation efficiency was 99.95%, and particle size smaller than 2,560 µm. The lipid profile highlighted in the microencapsulated oil was the medium-chain lauric fatty acid (C12:0) with 23.53% and the monounsaturated oleic fatty acid (C18:1) with 16.26%. The results for acidity (0.70 mg KOH/g) and peroxide (not identified) are in accordance with the legislation foreseen for oils and fats. In conclusion, the study demonstrates that it is possible to microencapsulate bacuri almond oil with a high percentage of efficiency, and being an alternative for the preservation of lipid compounds..